Ketamine also decreases serum BDNF levels and spatial learning while causes apoptosis in neonatal rats - Ozer, A. B.; Ceribasi, S.; Ceribasi, A. O.; Demirel, I.; Bayar, M. K.; Ustundag, B.; Erhan, O. L. (Univ Hospital Ospedali Riuniti, 2018)
Introduction The aim of this study were investigate the effects of early and late of ketamine in the neonatal rats. Material and methods The study included a total of 24 seven-day-old male Wistar-Albino rats. Subjects were randomly divided into two groups: Group C and Group K. In Group K, anesthesia was achieved with intraperitoneal administration of 4 doses of 20 mg/kg ketamine in 90 minute intervals. Then, half of the subjects were sacrificed to determine the early effects of anesthetics (Group KE, Group CE), while the rest of the subjects were sacrificed 6 weeks after the application to determine the late effects of anesthesia (Group KL, Group CL). Serum BDNF levels were measured by ELISA; brain BDNF and caspase-3 levels were assessed immunohistochemically. The behavior, anxiety states and spatial learning abilities of the subjects during the long-term period were evaluated by using the plus arm test and the Morris water test, respectively. Results Serum BDNF levels had significantly lower in Group KE (p<0.05). BDNF levels in the cerebral cortex and hippocampus was no significant difference between groups. There was a significant negative correlation between serum and cortex BDNF levels (p=0.01, r=0.601). Cortex caspase-3 levels were significantly higher in Groups KE than Group CE (p<0.05). There was no difference between groups in terms of open arm index, locomotor activity and Morris water tests. When the platform was removed, the time spent in the quadrant was significantly shorter Group KL (p<0.05). Conlcusions Ketamine effect on spatial learning maybe by reducing the serum BDNF levels and/or increasing apoptosis.
Keywords: anesthesia; apoptosis; brain derived neurotrophic factor; ketamine; learning